СОЦІАЛЬНИЙ КОМПЛАЄНС ЯК ІНСТРУМЕНТ ВИЖИВАННЯ У НАДЗВИЧАЙНИХ УМОВАХ ВОЄННОГО СТАНУ - Галушка, Зоя Іванівна; Галушка, Зоя Іванівна (КНЕУ, 2025)
The full-scale war in Ukraine has fundamentally transformed the conditions of business operation, making social compliance a vital instrument of survival and resilience. It ensures not only legal and ethical adherence but also social flexibility — the ability to preserve human capital, support employees, and maintain public trust. In wartime, social compliance expands beyond corporate ethics to include the protection of workers’ rights, inclusion of internally displaced persons, veterans, and people with disabilities, and the provision of psychological support. Companies that integrate social compliance into their crisis management strategies strengthen their reputation, reduce investment risks, and contribute to the implementation of ESG principles and sustainable development goals. Therefore, in the context of martial law, social compliance becomes a key mechanism for maintaining social stability, business sustainability, and moral leadership in society
SOCIAL COMPLIANCE AS A TOOL FOR SURVIVAL UNDER THE EXTRAORDINARY CONDITIONS OF MARTIAL LAW
Keywords: ocial compliance, wartime economy, resilience, business ethics, ESG standards, sustainable development, corporate responsibility, human capital, inclusiveness, Ukraine, martial law, trust, social sustainability